The role of platelets in acute kidney injury - Jansen, Marcel P B; Florquin, Sandrine; Roelofs, Joris J T H (Nature reviews. Nephrology, 2018)
Acute kidney injury (AKI), a major public health problem associated with high mortality and increased risk of progression towards end-stage renal disease, is characterized by the activation of intra-renal haemostatic and inflammatory processes. Platelets, which are present in high numbers in the circulation and can rapidly release a broad spectrum of bioactive mediators, are important acute modulators of inflammation and haemostasis, as they are the first cells to arrive at sites of acute injury, where they interact with endothelial cells and leukocytes. Diminished control of platelet reactivity by endothelial cells and/or an increased release of platelet-activating mediators can lead to uncontrolled platelet activation in AKI. As increased platelet sequestration and increased expression levels of the markers P-selectin, thromboxane A , CC-chemokine ligand 5 and platelet factor 4 on platelets have been reported in kidneys following AKI, platelet activation likely plays a part in AKI pathology. Results from animal models and some clinical studies highlight the potential of antiplatelet therapies in the preservation of renal function in the context of AKI, but as current strategies also affect other cell types and non-platelet-derived mediators, additional studies are required to further elucidate the extent of platelet contribution to the pathology of AKI and to determine the best therapeutic approach by which to specifically target related pathogenic pathways.